Relationship between Gastroesophageal Reflux Disease Questionnaire (GERD-Q) Score and Reflux Oesophagitis in Gastroesophageal Reflux Disease (GERD) Suspected Patients in Bandung - Dosmer Oloan Simarmata; Yudi Wahyudi; Muhammad Begawan Bestari; Rudi Supriadi (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy, 2020)
Background: Gastroesophageal reflux disease is a disease with heterogen symptoms, with no gold standard available to diagnose this condition. Questionnaire is a diagnostic tool that may enable an objective symptom assessment. GERD-Q questionnaire consist of 6 components of questions, formed from 4 various components of reflux symptoms (positive predictors of GERD) and 2 as negative predictors of GERD. This study aimed to observe the relationship between GERD-Q score and reflux oesophagitis in GERD suspected patients.